Drift‐Bounce Resonance Between Pc5 Pulsations and Ions at Multiple Energies in the Nightside Magnetosphere: Arase and MMS Observations. Issue 15 (3rd August 2018) - Oimatsu, S.; Nosé, M.; Teramoto, M.; Yamamoto, K.; Matsuoka, A.; Kasahara, S.; Yokota, S.; Keika, K.; Le, G.; Nomura, R.; Fujimoto, A.; Sormakov, D.; et al.
Abstract: A Pc5 wave is observed by the Exploration of energization and Radiation in Geospace Arase satellite in the inner magnetosphere ( L 5.4–6.1) near postmidnight ( L ‐magnetic local time 1.8–2.5 hr) during the storm recovery phase on 27 March 2017. Its azimuthal wave number ( m ‐number) is estimated using two independent methods with satellites and ground observations to be −8 to −15. The direct measurement of the m ‐number enables us to calculate the resonance energy. The flux oscillations of H + and O + ions at ≥ 56.3 keV are caused by drift resonance and those of O + ions at ≤ 18.6 keV by bounce resonance. Resonances of O + ions at multiple energies are simultaneously observed for the first time. The enhancement of the O + /H + flux ratio at ≤ 18.6 keV indicates selective acceleration of O + ions through bounce resonance. Plain Language Summary: Geomagnetic pulsations are magnetic fluctuations excited by solar wind or plasma instabilities in the magnetosphere. Pc5 waves are continuous geomagnetic pulsations with a period of 150–600 s. A Pc5 wave was observed in the inner magnetosphere during a magnetic storm on 27 March 2017. It propagated westward with a wave number of 8 to 15 and resonated with charged particles, resulting in oscillations of the H + and O + ion fluxes at ≥ 56.3 keV and the O + ion fluxes at ≤ 18.6 keV. Resonances of O + ions at multiple energies are simultaneously observed for the first time. At the same time, the O + /H + flux ratio at ≤ 18.6 keV enhanced corresponding to the O + ion flux oscillations, which indicates selective acceleration of O + ions through resonances. Key Points: A large‐amplitude Pc5 wave is observed by Arase and MMS1 in the postmidnight region at L > 5.4 during the storm recovery phase We estimate the m ‐number of the Pc5 wave to be −8 to −15 by using two independent methods with satellites and ground observations We simultaneously observe the drift resonance for H + and O + ions at ≥ 56.3 keV and bounce resonance for O + ions at ≤ 18.6 keV